2020
DOI: 10.1002/agj2.20179
|View full text |Cite
|
Sign up to set email alerts
|

Soil and terrain properties that predict differences in local ideal seeding rate for soybean

Abstract: The agronomic optimum seeding rate (AOSR) of soybean [Glycine max (L.) Merr.] varies based on environment. Understanding where AOSR varies within a field is useful for farmers utilizing variable rate seeding technology. An AOSR representing an area smaller than a whole field is referred to as local ideal seeding rate (LISR). The objective of this study was to identify soil and terrain properties that were most predictive of differences in LISR. Seeding rate trials were established at four fields in 2017 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…As an alternative to delineating management zones based on soil map unit, soil characteristics, yield history, or a combination of these factors, terrain properties may be a more useful option. Matcham et al (2020) found terrain properties, including aspect, hillshade, and elevation, to be better predictors of optimum seeding rate than soil properties. Terrain properties strongly influence water availability and movement and temperature (Hanna et al, 1982), which subsequently impact soybean growth and yield.…”
Section: Management Zonesmentioning
confidence: 93%
See 1 more Smart Citation
“…As an alternative to delineating management zones based on soil map unit, soil characteristics, yield history, or a combination of these factors, terrain properties may be a more useful option. Matcham et al (2020) found terrain properties, including aspect, hillshade, and elevation, to be better predictors of optimum seeding rate than soil properties. Terrain properties strongly influence water availability and movement and temperature (Hanna et al, 1982), which subsequently impact soybean growth and yield.…”
Section: Management Zonesmentioning
confidence: 93%
“…In the early adoption of VRS for soybean production, field characteristics such as soil map unit, soil P, and soil organic matter were identified as important factors when creating management zones (Smidt et al, 2016). Landscape properties, such as valley depth and general curvature, could also be used to create seeding rate management zones within fields (Matcham et al, 2020). In practice, soybean farmers use a variety of methods to make VRS management zones, including soil properties and yield history, and generally plant fewer seeds in highly productive zones and more seeds in less productive zones, which is opposite of VRS in corn (Carciochi et al, 2019;Devlin et al, 1995;Gaspar et al, 2020;Grisso et al, 2009).…”
mentioning
confidence: 99%
“…ppm, parts per million index. Terrain attributes were used as covariates in the GWR and RF models.Geographically weighted regressions were run in SAGA GIS according to the procedures detailed inMatcham et al (2020) with a Guassian kernel and bandwidth = 1. Random forest models were built by the package randomForest within R (3.4.2) with the parameters ntree = 500 and mtry = 2, which are the values recommended by the package for a dataset of our size…”
mentioning
confidence: 99%